Phthalate diversity in eggs and associations with oxidative stress in the European herring gull (Larus argentatus). (August 2021) - Allen, Simon F.; Ellis, Francesca; Mitchell, Christopher; Wang, Xianyu; Boogert, Neeltje J.; Lin, Chun-Yin; Clokey, Joseph; Thomas, Kevin V.; Blount, Jonathan D.
Abstract: Phthalates are plastic-derived contaminants that are ubiquitous in natural environments and function as pro-oxidants. The extent to which phthalates bioaccumulate in wild animals and associations with oxidative stress are poorly understood. Here, we describe relationships between maternally-derived phthalates, lipid peroxidation (malondialdehyde, MDA) and the dietary antioxidant α-tocopherol in eggs of European herring gulls ( Larus argentatus ) in Cornwall, UK. Up to six phthalate parent compounds and four phthalate metabolites were detected. Egg concentrations of MDA were positively associated with dicyclohexyl phthalate (DCHP) and negatively associated with α-tocopherol, suggesting that DCHP is associated with oxidative stress in gulls. The consequences of phthalate exposure in ovo for offspring development warrants study. Highlights: Several phthalate compounds detected in eggs of European herring gull DCHP correlated positively with lipid peroxidation and negatively with vitamin E Phthalate exposure is associated with oxidative stress.